2017
DOI: 10.1016/j.jart.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

New acid dyes and their metal complexes based on substituted phenols for leather: Synthesis, characterization and optical studies

Abstract: The present investigation deals with synthesis of new acid dyes from 4-amino-1-(4-sulfophenyl)-3-methyl-5-pyrazolone and phenol derivatives and their metal complexes (Cu (II) and Fe (II)). The phenol derivatives include 4-chlorophenol, 4-nitrophenol, 4-hydroxybenzene sulfonic acid, 2-nitrophenol-4-sulfonic acid, resorcinol and bisphenol A and bisphenol S. The newly synthesized dyes were applied to crust leather to assess their dyeing properties. The fastness properties of unmetallized dyes were less as compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 10 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…Additionally, as dye complexes with different metals give different colours, dye structure may be altered. 128 Other challenges for biogenic dyes could be limited stability in the conventional dyeing process or low water solubility. Studies reported insufficient stability to high temperatures or extreme pH values faced in the dyeing process.…”
Section: Undesired Properties Of Biogenic Compoundsmentioning
confidence: 99%
“…Additionally, as dye complexes with different metals give different colours, dye structure may be altered. 128 Other challenges for biogenic dyes could be limited stability in the conventional dyeing process or low water solubility. Studies reported insufficient stability to high temperatures or extreme pH values faced in the dyeing process.…”
Section: Undesired Properties Of Biogenic Compoundsmentioning
confidence: 99%
“…11,12 Metal azo dye complexes are used in dying leather. 13,14 Pyridine derivatives exhibit significant contribution in several biochemical reactions. Pyridine ring molecular systems having chelating molecular designs, have been examined in the field of mycology for developing metal-based drugs.…”
Section: Introductionmentioning
confidence: 99%
“…e trans isomer is stable which converts to cis isomer under the light, when the process is perfectly reversible calling photochromic [5]. When this process is accompanied by a significant change in the dipole moment, that qualifies the material to be a candidate for high optic data storage [6]. e azo dye complexes such as azo quinoline dye and its complexes and rhenium complex based on the azo dye of iminopyridine exhibited significant nonlinear optical properties, and these properties play an important role in optical data storage and telecommunications [7][8][9].…”
Section: Introductionmentioning
confidence: 99%